2022
DOI: 10.1007/s43440-022-00355-2
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral drug research for Japanese encephalitis: an updated review

Abstract: Japanese encephalitis (JE) caused by the Japanese encephalitis virus (JEV) is one of Asia's most common viral encephalitis. JEV is a flavivirus, common in rural and sub-urban regions of Asian countries. Although only 1% of JEV-infected individuals develop JE, there is a 20–30% chance of death among these individuals and possible neurological sequelae post-infection. No licensed anti-JE drugs are currently available, despite extensive efforts to develop them. Literature search was performed using databases such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 165 publications
(275 reference statements)
0
11
0
Order By: Relevance
“…These proteins are crucial for the entry, maturation, replication, and release of virus in the host cells 6 . Envelope, nonstructural protein‐1, JEV protease, helicase/nucleoside triphosphatase, and RNA‐dependent RNA polymerase (NS5) of JEV have been targeted to design direct antiviral agents against JEV 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins are crucial for the entry, maturation, replication, and release of virus in the host cells 6 . Envelope, nonstructural protein‐1, JEV protease, helicase/nucleoside triphosphatase, and RNA‐dependent RNA polymerase (NS5) of JEV have been targeted to design direct antiviral agents against JEV 7 …”
Section: Introductionmentioning
confidence: 99%
“…6 Envelope, nonstructural protein-1, JEV protease, helicase/nucleoside triphosphatase, and RNA-dependent RNA polymerase (NS5) of JEV have been targeted to design direct antiviral agents against JEV. 7 Therefore, in pursuit of anti-JEV agents, we searched the Indian Medicinal Plants, Phytochemistry, and Therapeutics (IMPPAT) and PubMed databases for medicinal plants having "antiviral" and "antiinflammatory" activities. 8 We have found that Andrographis paniculata, Berberis lycium, Curcuma longa, and Vitis vinifera possess both activities, and the key chemical constituents present in these plants were identified as andrographolide, berberine, curcumin, resveratrol, and retinoic acid, respectively (Table S1).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies performed by administering the potential agents at the early stages of the infection failed to give a promising therapy. 131 Pentoxifylline which is an anti-TNF agent has shown 100% recovery of a mice model at a dose value of 200 mg/ kg. 132 Another such drug is arctigenin which is lignan of Asteraceae plants that has also shown 100% recovery at a dose of 20 mg/kg but only with immediate (1 day of infection) administration.…”
Section: Anti-viral Agents For Jementioning
confidence: 99%
“…Coming to the therapy for encephalitis, initially the agents with profound efficacy against the JE infection were very few, due to the infection complexity and difficulties in understanding the disease invasion. Most of the studies performed by administering the potential agents at the early stages of the infection failed to give a promising therapy 131 . Pentoxifylline which is an anti‐TNF agent has shown 100% recovery of a mice model at a dose value of 200 mg/kg 132 .…”
Section: Treatment For Jementioning
confidence: 99%
“…Humans and horses are considered to be dead-end hosts [ 6 ]. The prevalence of JEV shows specific distribution characteristics on the geographical scale, seasonal scale, climate scale, and population scale [ 7 ]. In temperate and subtropical regions, populations in agricultural areas are the primary populations exposed to JEV with the onset of the rainy season, among which, unvaccinated populations and children are at high risk of JEV infection.…”
Section: Introductionmentioning
confidence: 99%